Plankton-feeding aggregation and occasional cleaning by adult butterflyfish, Chaetodon striatus (Chaetodontidae), in Southwestern Atlantic - Sazima, Cristina [UNESP]; Sazima, Ivan (My University, 2001)
Butterflyfishes of the genus Chaetodon (Chaetodontidae) are mostly bottom-feeders, and juveniles of some Pacific species are known to clean other fish. Herein we report on occasional cleaning by adult individuals of the Western Atlantic butterflyfish Chaetodon striatus, during their plankton-feeding aggregation. Four species of reef fish solicited cleaning to the butterflyfish amidst the aggregation.
Keywords: ASW; Brazil; Chaetodon striatus; Chaetodontidae; Cleaning behaviour; Group feeding; Planktivory